Stability and dynamics of size-structured freshwater communities along environmental gradients - Dijoux, Samuel (Jihočeská univerzita, 2023)
This thesis focuses on the dynamics and stability of size-structured communities in freshwater in response to environmental stressors. It reviews the influences of anthropogenic stressors on the stability, structure and diversity of freshwater communities, with a particular focus on the multiscale influences of rising temperature and nutrient enrichment. The three main chapters use recent advances in food web theory to explore the dynamics, stability and structure of communities under multiple threats (species invasions, nutrient enrichment and warming). The theoretical outcomes provide robust predictions for ecologists to link individual-level responses to global patterns observed at community scale. This thesis demonstrates the importance of considering species traits (body size, trophic position, performance of vital rates) and life histories to improve predictions on future responses to environmental stressors and to develop appropriate conservation measures.
Stability and dynamics of size-structured freshwater communities along environmental gradients
Keywords: warming; eutrophication; species invasions; food webs; freshwater communities; community dynamics; metabolic ecology; emergent Allee effect; body size; life history trait; warming; eutrophication; species invasions; food webs; freshwater communities; community dynamics; metabolic ecology; emergent Allee effect; body size; life history trait